1994
DOI: 10.1111/j.1365-2249.1994.tb06133.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycation of monoclonal antibodies impairs their ability to bind antigen

Abstract: SUMMARYAs elevated levels of glycated IgG have been detected in the plasma of patients with diabetes mellitus, a disease associated with increased susceptibility to infection, we have investigated whether glycation of MoAbs affects the kinetics and/or affinity of antigen binding. Three mouse MoAbs were incubated with 0-5 M glucose at pH 7-4 for 14-21 days at 37°C. Control MoAbs were incubated using identical conditions but with no added glucose. Using a surface plasmon resonance technique we found that glycati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Glycation of IgG is of special interest due to its influence on the functionality of immunoglobulin's and overall immunocompetence. Several studies showed the extent of glycation of IgG and its influence on the biological functionality of IgG [5][6][7][8][9][10][11][12][13], but the immunological role of AGEs damage IgG (AGE-IgG) in patients with type 1 DM is still not fully understood. Proper extensive clinical investigation of this aspect with a high level of confidence are needed.To meet this need, we hypothesized that AGE-IgG helps to initiate autoimmunity in type 1 diabetes mellitus patients.…”
Section: Introductionmentioning
confidence: 99%
“…Glycation of IgG is of special interest due to its influence on the functionality of immunoglobulin's and overall immunocompetence. Several studies showed the extent of glycation of IgG and its influence on the biological functionality of IgG [5][6][7][8][9][10][11][12][13], but the immunological role of AGEs damage IgG (AGE-IgG) in patients with type 1 DM is still not fully understood. Proper extensive clinical investigation of this aspect with a high level of confidence are needed.To meet this need, we hypothesized that AGE-IgG helps to initiate autoimmunity in type 1 diabetes mellitus patients.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of nonenzymatically glycosylated total plasma proteins, albumin and IgG have been measured in the diabetics and non-diabetics patients in past (26)(27)(28)(29) and a significant increase in both glycosylated albumin and IgG, in diabetics were reported. These evidences also support our present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Glycation occurs at a number of sites and can be produced by forced stress conditions (95.4% overall glycation), and physiological cell culture antibody manufacturing conditions (10-40% glycation). 5,8,37,64,65 It is evident that glycation levels increase in stress exposure conditions with increased sugar concentration in the formulation, higher storage temperature, and time in storage. The glycation sites in mAbs manufactured under normal cell culture conditions with standard physiological parameters, such as temperature and pH, with elevated glucose levels, are similar to endogenous antibodies.…”
Section: Effects On Biological Functionmentioning
confidence: 99%
“…The glycation sites in mAbs manufactured under normal cell culture conditions with standard physiological parameters, such as temperature and pH, with elevated glucose levels, are similar to endogenous antibodies. 8,37 The effect of glycation on antibody activities ranged from no effect 5,8,37,65 to loss of activity, 64,66 although typically mAb glycation does not appear to substantially affect antibody binding activities. The effects of AGEs on antibodies have not been reported; however, it was reported that AGEs could potentially reduce the activity of the therapeutic protein interferon alfacon-1.…”
Section: Effects On Biological Functionmentioning
confidence: 99%
See 1 more Smart Citation